2012
DOI: 10.1177/1087057112454741
|View full text |Cite
|
Sign up to set email alerts
|

Novel Stem Cell–Based Drug Discovery Platforms for Cardiovascular Disease

Abstract: The complexity and diversity of many human diseases pose significant hurdles to the development of novel therapeutics. New scientific and technological advances, such as pharmacogenetics, provide valuable frameworks for understanding genetic predisposition to disease and tools for diagnosis and drug development. However, another framework is emerging based on recent scientific advances, one we suggest to call pharmacoempirics. Pharmacoempirics takes advantage of merging two nascent fields: first, the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 125 publications
0
4
0
Order By: Relevance
“…Coupling of pharmacogenomics and iPSC technology is still in its infancy, but in recent years, the technology used to understand cardiovascular diseases has improved, mainly through the use of patient iPSC‐derived cardiomyocytes (iPSC‐CMs) [16, 17]. Moretti et al [18] used iPSC‐CMs to elucidate mutations related to long QT syndrome; Zhi et al [19] combined whole‐exome sequencing and iPSC‐CMs to study left ventricular hypertrophy, a heritable predictor for cardiovascular disease in African Americans; and Lan et al [20] demonstrated pharmacological restoration of function in iPSC‐CMs from patients with inherited cardiomyopathies.…”
Section: Introductionmentioning
confidence: 99%
“…Coupling of pharmacogenomics and iPSC technology is still in its infancy, but in recent years, the technology used to understand cardiovascular diseases has improved, mainly through the use of patient iPSC‐derived cardiomyocytes (iPSC‐CMs) [16, 17]. Moretti et al [18] used iPSC‐CMs to elucidate mutations related to long QT syndrome; Zhi et al [19] combined whole‐exome sequencing and iPSC‐CMs to study left ventricular hypertrophy, a heritable predictor for cardiovascular disease in African Americans; and Lan et al [20] demonstrated pharmacological restoration of function in iPSC‐CMs from patients with inherited cardiomyopathies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in vitro analyses with PS-iPSC-derived cells may contribute to the prediction of drug efficacy and side effects in a personalized fashion. In this regard, pharmaceutical companies have already recognized that iPSC-cardiomyocytes can provide a high-quality platform for drug toxicity screening [ 67 , 68 , 69 , 70 , 71 ]. Many new drugs have unexpected cardiac toxicity resulting in sudden cardiac death, which can lead to decisions to abort drug development.…”
Section: Disease Modeling Using Patient-specific Induced Pluripotementioning
confidence: 99%
“…Because of the importance of TGF-b signaling in endothelial to mesenchymal transitions (EndMT) and the role of this process in postmyocardial infarction (MI) cardiac fibrosis (von Gise and Pu 2012), it will be very exciting to test these compounds for their effects in in vivo MI models. There are many more such examples including patient-derived macrophages for reverse cholesterol transport (RCT) and endothelial cell activation and cholesterol uptake assays for vascular therapies to name only a few (Adams and García-Cardeña 2012).…”
Section: Human Disease-relevant Cell-based Modelsmentioning
confidence: 99%